Correction: Self-supported Co3O4 nanoneedle arrays decorated with PPy via chemical vapor phase polymerization for high-performance detection of trace Pb2+. Issue 16 (12th April 2017) - Wang, Wenjing; Wang, Chao; Dou, Peng; Zhang, Lifang; Zheng, Jiao; Cao, Zhenzhen; Xu, Xinhua
Abstract : Correction for 'Self-supported Co3 O4 nanoneedle arrays decorated with PPy via chemical vapor phase polymerization for high-performance detection of trace Pb 2+ ' by Wenjing Wang et al., Anal. Methods, 2017, 9, 1905–1911.